A welfare state funded by nature and OPEC. A guided tour on Norway's path from an exceptionally impressive to an exceptionally strained fiscal position - Kim Massey Heide; Erling Holmøy; Ingeborg Foldøy Solli; Birger Strøm (Statistics Norway, Research Department, 2006)
Large petroleum revenues make Norway an enviable fiscal loner. The fiscal policy rule adopted from 2001 transforms petroleum wealth into foreign assets, and only the real return on the financial fund should be spent annually. Despite this ambitious saving of the petroleum wealth, we find it unlikely that present tax rates and welfare schemes are sustainable in a long run perspective. Rather, the results from combining detailed models of demography and government expenditures with a detailed CGE model, suggest that Norway is exceptional also with respect to strong growth in government expenditures. In our baseline scenario the payroll tax rate must be increased continuously when ageing sets in after 2020, passing twice the present level about 2045. This is required even if the pension fund reaches 1.4 times GDP, commanding an unprecedented degree of fiscal discipline.
Keywords: H30; H55; H62; 330; Population ageing; Fiscal sustainability; Computable general equilibrium model; Dynamic micro simulation